Le sub judice - Deslauriers, Ignace J. (Assurances)

(untitled) (HEC Montréal, 1987)
We would like to thank Mr. Ignace J. Deslauriers for his very concise examination of the so-called sub judice rule. While the article brings to light many interesting points, it should be understood that to render a decision, a magistrate, as well as the jury, must be given complete freedom of action, without outside interference.